Analysis of Electrical Energy Potential from Palm Oil Frond Bioethanol: Case Study of North Bagan Sinembah Village Rokan Hilir Regency, Riau - Ariyanda Lubis; Marhama Jelita (Advance Sustainable Science Engineering and Technology, 2025)
North Bagan Sinembah village in Riau province contributes a land area of ​​7.376,4443 ha which produces frond biomass 6,3 tons of oil palm fronds per year, North Bagan Sinembah Village so far has not had access to PLN electricity and only uses a generator with a running time of 6 hours per day. This research aims to find the electricity needs of North Bagan Sinembah village with a homogeneous sample, the sampling method used is simple random sampling. This research too test the potential of palm frond bioethanol using the fermentation method using the SuperPro Designer application, calculate potential energy and electrical power with method from a variety of mixed fuels E10%, E30%, E50%, E100%. The electricity needs of North Bagan Sinembah Village are 867,62 kWh with volumetric flow potential of 15,72 L/ha/day, 1.641,66 L/ha/month and 18.053,72 L/ha/year. By using a variety of fuel mixtures E10 produce 172,68 kWh/day, 5.261,88 kWh/month, 57.866,3 kWh/year. E30 produce 161,77 kWh/day, 4.855,16 kWh/month, 53.392,6 kWh/year. E50 produce 1.632,9 kWh/day, 50.400,66 kWh/month, 538.747,9 kWh/year and E100 produces electrical power of 1,257.30 kWh/day, 38,808.48 kWh/month, 414,835.88 kWh/year. The potential electrical power for the fuel mixture is E10 4,144.32 Watts/day, 126,285.12 Watts/month, 1,388,791.2 Watts/year. E30 produces 3,882.48 Watts/day, 116,523.84 Watts/month, 1,281,422.4 Watts /year, E50 39,189.6 Watts/day, 1,209,615.84 Watts/month, 12,929,949.6 Watts/year and E100 produces 30,175.2 Watts/day, 931,403.52 Watts/month, 9,956,061.12 Watts/year. It can be concluded that with variations in the fuel mixture of dexlite and ethanol at each percent of the mixture, it has a large potential for E50 (50% Dexlite and 50% ethanol) per year of 12,929,949.6 watts, due to harvesting palm fronds twice a month, the production bioethanol is carried out every month with a potential electrical power of 1,209,615.84 watts/month.